Preparation method of TiAl alloy surface high-temperature oxidation-resistant wear-resistant coating
By combining ultrasonic impact strengthening and double glow metal seepage technology on the surface of TiAl alloy, a nanocrystal modified layer is formed to promote the infiltration of Zr-Cr-Y elements, and the problem of insufficient high-temperature oxidation performance of TiAl alloy is solved and high-temperature oxidation resistance is achieved and significantly improve wear resistance.
Patent Information
- Application Number
- CN202411357102.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
When TiAl alloy is oxidized at a high temperature above 800°C, the oxide film generated on the surface is loose and cannot effectively prevent the diffusion of oxygen, resulting in insufficient antioxidant performance. The coating composition and thickness of existing Shuanghui Plasma Metallurgy are insufficient, which affects its performance.
Combined with ultrasonic impact enhancement and double glow metal seepage process, a nano-sized grain-modified layer is formed to promote the infiltration of Zr-Cr-Y alloy elements, and a coating with high temperature, oxidation and wear resistance is prepared to improve the coating thickness and performance. .
It significantly improves the high-temperature oxidation resistance and wear resistance of the coating, increases the coating thickness, reduces the oxygen diffusion coefficient, ensures that the coating does not peel after oxidation at high temperatures above 1000°C for 100 hours, and extends the use of TiAl alloy life.
Smart Images

Figure CN119243081A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultrasonic strengthening and double glow plasma metallurgy preparation, and specifically relates to a method for preparing a high-temperature oxidation-resistant and wear-resistant coating on the surface of a TiAl alloy. Background Art
[0002] TiAl-based alloy is one of the most studied intermetallic compounds. It has the characteristics of high specific strength, large specific elastic modulus and good creep resistance. Its high-temperature mechanical properties are similar to those of Ni-based high-temperature alloys, and its specific gravity is only half of that of Ni-based high-temperature alloys. It is a high-temperature structural material with great potential to replace Ni-based high-temperature alloys, and is one of the most attractive materials for the preparation of aircraft structural parts and turbine engines. The working environment of aircraft engine blades is at high temperature (800℃~1100℃), high speed and complex stress. The material is required to have good high-temperature strength, creep endurance, fatigue performance and organizational stability. At the same time, it also puts forward high requirements for the high-temperature oxidation resistance and friction and wear resistance of the matrix material. However, when oxidized at high temperature above 800℃, a mixed oxide film of TiO2 and Al2O3 will be generated on the surface of TiAl alloy. The large amount of TiO2 doping will lead to a loose structure of the mixed oxide film, which cannot prevent the diffusion of oxygen. Therefore, the improvement of the oxidation resistance of TiAl alloy above 800℃ has become an urgent problem to be solved.
[0003] Surface treatment is an effective method to improve the high temperature oxidation resistance and wear resistance of TiAl alloy. Through surface modification of TiAl alloy, a surface modification layer with high temperature oxidation resistance can be formed on the surface of TiAl alloy without affecting the performance of the base material. The basic conditions that should be met to prepare an ideal coating are: first, the coating has good bonding performance with the base, second, there is a certain compatibility between the coating and the base, third, a continuous and dense oxide film can be formed on the surface of the coating during high temperature oxidation, and fourth, the coating has little effect on the alloy base.
[0004] The double-layer glow plasma metallization technology is carried out under low vacuum. The argon ions formed by the glow discharge of the source and anode are used to bombard the source target. The alloy elements sputtered from the source material are deposited and diffused onto the surface of the material to be infiltrated, forming a modified layer of the metal to be infiltrated on the surface of the material. The composition and properties of the infiltrated layer can be changed by changing the process parameters such as the source voltage, cathode voltage, insulation temperature, insulation time, inter-electrode spacing, and air pressure. The alloying layer is prepared by the double-glow plasma metallization technology, and any solid metal element or a mixture of solid metal elements in the periodic table can be infiltrated to form an alloy layer with excellent high-temperature mechanical strength and good corrosion resistance on the surface of the substrate. Compared with other surface alloying technologies, the double-glow plasma metallization technology has the characteristics of being able to prepare a gradient alloy layer, controllable alloy layer thickness and structure, a wide range of infiltrated elements, good infiltration layer quality, and no hydrogen embrittlement and oxidation problems. This technology has successfully prepared high-performance gradient alloy layers on the surfaces of carbon steel, ductile iron, nickel-based alloys, titanium alloys and TiAl-based alloys, improving the wear resistance, corrosion resistance and high-temperature oxidation resistance of the substrate surface. However, the composition of the coating prepared using the double-glow technology is quite different from that of the target material, and the coating thickness is also relatively thin, which will affect the performance of the coating to a certain extent. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-temperature oxidation-resistant and wear-resistant coating on the surface of a TiAl alloy in view of the deficiencies of the above-mentioned prior art. The method combines ultrasonic impact strengthening with a double glow metallization process to form a nano-sized grain modification layer on a TiAl alloy substrate, promotes the penetration of various elements into the TiAl alloy during the double glow metallization process, prepares a wear-resistant and oxidation-resistant coating with excellent performance and increases the coating thickness, improves the high-temperature oxidation resistance and wear resistance of the coating, and solves the problem that the coating prepared by the existing double glow plasma metallurgy has large composition differences and thin coating thickness, which affects its performance.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-temperature oxidation-resistant and wear-resistant coating on the surface of a TiAl alloy, characterized in that the method comprises the following steps:
[0007] Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy to remove the surface oxide layer, then perform ultrasonic cleaning to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used;
[0008] Step 2: performing ultrasonic impact strengthening on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer;
[0009] Step 3: Grind, clean and dry the TiAl alloy with the modified layer in step 2, and then place it as a substrate on the workbench of the double glow plasma metallurgical equipment. Use Zr-Cr-Y alloy as the target and adopt double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metal-infiltrated coating. After cooling, take it out to obtain a TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface.
[0010] The present invention firstly performs ultrasonic impact strengthening on the impact surface of the TiAl alloy to be used after being polished, cleaned and blown dry, and forms a nano-sized grain modification layer on the surface of the TiAl alloy by ultrasonic impact strengthening. Since the nano-crystals of the surface modification layer have high surface energy, the adsorption capacity of the atoms to be infiltrated can be enhanced during the adsorption process, and the high-density grain boundaries and dislocations of the nano-crystals can also provide more short-range rapid diffusion channels for the atoms to be infiltrated when they diffuse inward, thereby effectively increasing the diffusion speed and reducing the diffusion temperature. Based on the effect of the ultrasonic impact strengthening, in the subsequent When Zr-Cr-Y alloy is used as the target material and the double glow plasma metallization process is adopted to perform surface metallization treatment on TiAl alloy, the penetration of various elements in the target material, especially the Zr element, into the TiAl alloy is promoted. The mass content of the Zr element in the coating can usually be increased to 35%, which is much higher than the mass content of the Zr element in the coating prepared by the double glow plasma metallization process alone, which is 7%. It not only increases the coating thickness, but more importantly, helps the coating to form a ZrO2 oxide film during the oxidation process, thereby reducing the oxygen diffusion coefficient of the coating, thereby improving the high temperature oxidation resistance and wear resistance of the coating.
[0011] The above-mentioned method for preparing a high-temperature antioxidant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the polishing treatment in step one is performed using a surface grinder, the ultrasonic cleaning is performed using an ultrasonic cleaning machine filled with anhydrous ethanol, and the ultrasonic cleaning time is 20 minutes.
[0012] The above-mentioned method for preparing a high-temperature antioxidant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the step distance of the ultrasonic impact strengthening in step 2 is 0.06 mm, the pressure is 0.4 MPa, the number of impacts is 1 to 30 times, the frequency is 20 kHz to 30 kHz, and the amplitude is 5 μm to 10 μm.
[0013] The above-mentioned method for preparing a high-temperature antioxidant and wear-resistant coating on the surface of a TiAl alloy is characterized in that in step three, the TiAl alloy with a modified layer is polished using 400#, 800#, and 1000# sandpapers in sequence, and then ultrasonically cleaned with deionized water for 5 minutes, and then ultrasonically cleaned with an ethanol solution for 5 minutes, and blown dry with cold air for standby use.
[0014] The above-mentioned method for preparing a high-temperature oxidation-resistant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the Zr-Cr-Y alloy in step three is composed of the following components in percentage by mass: Zr 30% to 50%, Cr 45% to 75%, and Y 0.5% to 5%.
[0015] The present invention selects the Zr-Cr-Y alloy target composed of the above components to perform surface metallization treatment on the substrate to form a metal-infiltrated coating. First, the lattice structure and atomic radius of Zr in the alloy are similar to those of Ti. The Zr element can infinitely dissolve with α-Ti and β-Ti to form a substitution solid solution, which plays a role in solid solution strengthening for TiAl alloy; at the same time, Zr, as a component of the heat-strength Ti alloy, forms a dense ZrO2 oxide film on the Ti surface, and the ZrO2 oxide film has the characteristics of high chemical stability, high temperature resistance, corrosion resistance, small heat capacity and thermal conductivity, and good thermal insulation performance, which is beneficial to improving the high-temperature oxidation resistance of the coating. Secondly, the Cr in the alloy is an antioxidant metal, which can reduce the minimum Al content for the formation of Al2O3 film thermodynamically, increase the activity of Al, and thus promote the formation of Al2O3 oxide film, which is beneficial to improving the high-temperature oxidation resistance of the coating; at the same time, the Cr content is strictly controlled to avoid the formation of Laves phase and significantly increase the brittleness of the coating. In addition, an appropriate amount of rare earth element Y is added to the alloy to refine the grains and improve the mechanical properties of the coating. During the oxidation process, the Y-rich phase is segregated at the film-substrate interface to play a pinning role, which can improve the adhesion of the coating, reduce the oxidation rate of the TiAl alloy substrate, and also help improve the oxidation resistance and thermal shock resistance of the coating.
[0016] The above-mentioned method for preparing a high-temperature antioxidant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the process of surface metallization treatment described in step three is: open the argon valve to pass argon, turn on the power supply at the same time, adjust the air pressure to 30Pa~70Pa, the cathode voltage to 500V~700V, the source voltage to 800V~1000V, the insulation temperature to 800℃~950℃, and the insulation time to 3h~6h; the cooling is furnace cooling to below 150℃.
[0017] The above-mentioned method for preparing a high-temperature oxidation-resistant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the thickness of the high-temperature oxidation-resistant and wear-resistant coating in step three is 20 μm to 30 μm.
[0018] The above-mentioned method for preparing a high-temperature antioxidant and wear-resistant coating on the surface of a TiAl alloy is characterized in that the surface hardness of the TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface described in step three is 1500HV~1800HV, and the coating does not show delamination after high-temperature oxidation above 1000°C for 100h.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. The present invention combines ultrasonic impact strengthening with double glow metallization process. By first performing ultrasonic impact strengthening on the TiAl alloy substrate to form a nano-sized grain modification layer, the penetration of various elements in the Zr-Cr-Y alloy target into the TiAl alloy during the double glow metallization process is promoted, the coating thickness is increased, the oxygen diffusion coefficient of the coating is reduced, and the high-temperature oxidation resistance and wear resistance of the coating are improved.
[0021] 2. The present invention adopts Zr-Cr-Y alloy target to perform surface metallization treatment on TiAl alloy substrate to form metal infiltration coating, utilizes Zr element to play a role of solid solution strengthening, and forms ZrO2 oxide film to improve the high temperature oxidation resistance of coating, utilizes Cr to promote the formation of Al2O3 oxide film, improves the high temperature oxidation resistance of coating, utilizes Y element to improve the adhesion of coating, and further improves the oxidation resistance and thermal shock resistance of coating.
[0022] 3. The thickness of the high-temperature oxidation-resistant and wear-resistant coating prepared by the present invention is 20 μm to 30 μm, the surface hardness of the coating is 1500 HV to 1800 HV, the wear resistance is improved by more than 1 times, and the coating does not show delamination after high-temperature oxidation at above 1000°C for 100 hours, showing good high-temperature oxidation resistance, solving the problem of insufficient oxidation resistance of TiAl alloy when serving at high temperatures above 800°C, and further improving the service life of TiAl alloy.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a cross-sectional SEM image of the TiAl alloy with a high-temperature oxidation-resistant and wear-resistant coating on the surface prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0025] Example 1
[0026] This embodiment includes the following steps:
[0027] Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy using a surface grinder to remove the surface oxide layer, then place it in an ultrasonic cleaning machine filled with anhydrous ethanol for ultrasonic cleaning for 20 minutes to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used;
[0028] Step 2: ultrasonic impact strengthening is performed on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer; the step length of the ultrasonic impact strengthening is 0.06 mm, the pressure is 0.4 MPa, the number of impacts is 1, the frequency is 20 kHz, and the amplitude is 5 μm;
[0029] Step 3: polish the TiAl alloy with the modified layer in step 2 with 400#, 800# and 1000# sandpapers in turn, then ultrasonically clean it with deionized water for 5 minutes, then ultrasonically clean it with ethanol solution for 5 minutes, and blow dry it with cold air for later use;
[0030] Clean the double glow plasma metallurgical equipment and tooling, then place the spare TiAl alloy with the modified layer as a substrate on the workbench of the double glow plasma metallurgical equipment, use the Zr-Cr-Y alloy as the target, and adopt the double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metallized coating. The specific process is: open the argon valve to introduce argon, turn on the power supply at the same time, adjust the gas pressure to 30Pa, the cathode voltage to 500V, the source voltage to 800V, the insulation temperature to 800℃, the insulation time to 3h, close the argon valve after the insulation is completed, cool it to below 150℃ with the furnace and take it out to obtain a TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface; the Zr-Cr-Y alloy is composed of the following components in percentage by mass: Zr 30%, Cr 69.5%, and Y 0.5%.
[0031] After testing, the thickness of the high-temperature antioxidant and wear-resistant coating on the surface of the TiAl alloy in this embodiment is 20μm, the surface hardness of the TiAl alloy with the high-temperature antioxidant and wear-resistant coating on the surface is 1800HV, the wear resistance is improved by more than 1 times, and after high-temperature oxidation at above 1000°C for 100h, the surface shows slight discoloration, and the coating does not show delamination.
[0032] Example 2
[0033] This embodiment includes the following steps:
[0034] Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy using a surface grinder to remove the surface oxide layer, then place it in an ultrasonic cleaning machine filled with anhydrous ethanol for ultrasonic cleaning for 20 minutes to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used;
[0035] Step 2: ultrasonic impact strengthening is performed on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer; the step length of the ultrasonic impact strengthening is 0.06 mm, the pressure is 0.4 MPa, the number of impacts is 10 times, the frequency is 25 kHz, and the amplitude is 5 μm;
[0036] Step 3: polish the TiAl alloy with the modified layer in step 2 with 400#, 800# and 1000# sandpapers in turn, then ultrasonically clean it with deionized water for 5 minutes, then ultrasonically clean it with ethanol solution for 5 minutes, and blow dry it with cold air for later use;
[0037] Clean the double glow plasma metallurgical equipment and tooling, then place the spare TiAl alloy with the modified layer as a substrate on the workbench of the double glow plasma metallurgical equipment, use the Zr-Cr-Y alloy as the target, and adopt the double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metallized coating. The specific process is: open the argon valve to introduce argon, turn on the power supply at the same time, adjust the gas pressure to 30Pa, the cathode voltage to 500V, the source voltage to 800V, the insulation temperature to 850℃, the insulation time to 4h, close the argon valve after the insulation is completed, cool it to below 150℃ with the furnace and take it out to obtain a TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface; the Zr-Cr-Y alloy is composed of the following components in percentage by mass: Zr 24%, Cr 75%, and Y1%.
[0038] After testing, the thickness of the high-temperature antioxidant and wear-resistant coating on the surface of the TiAl alloy in this embodiment is 22μm, the surface hardness of the TiAl alloy with the high-temperature antioxidant and wear-resistant coating on the surface is 1200HV, the wear resistance is improved by more than 1 times, and the surface does not change color after high-temperature oxidation at above 1000°C for 100h, and the coating does not peel off.
[0039] Example 3
[0040] This embodiment includes the following steps:
[0041] Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy using a surface grinder to remove the surface oxide layer, then place it in an ultrasonic cleaning machine filled with anhydrous ethanol for ultrasonic cleaning for 20 minutes to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used;
[0042] Step 2: ultrasonic impact strengthening is performed on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer; the step length of the ultrasonic impact strengthening is 0.06 mm, the pressure is 0.4 MPa, the number of impacts is 15 times, the frequency is 25 kHz, and the amplitude is 8 μm;
[0043] Step 3: polish the TiAl alloy with the modified layer in step 2 with 400#, 800# and 1000# sandpapers in turn, then ultrasonically clean it with deionized water for 5 minutes, then ultrasonically clean it with ethanol solution for 5 minutes, and blow dry it with cold air for later use;
[0044] Clean the double glow plasma metallurgical equipment and tooling, then place the spare TiAl alloy with the modified layer as a substrate on the workbench of the double glow plasma metallurgical equipment, use the Zr-Cr-Y alloy as the target, and adopt the double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metallized coating. The specific process is: open the argon valve to introduce argon, turn on the power supply at the same time, adjust the gas pressure to 50Pa, the cathode voltage to 600V, the source voltage to 900V, the insulation temperature to 920℃, the insulation time to 6h, close the argon valve after the insulation is completed, cool it to below 150℃ with the furnace and take it out to obtain a TiAl alloy with a high-temperature oxidation-resistant and wear-resistant coating on the surface; the Zr-Cr-Y alloy consists of the following components in percentage by mass: Zr 50%, Cr 45%, and Y5%.
[0045] After testing, the thickness of the high-temperature antioxidant and wear-resistant coating on the surface of the TiAl alloy in this embodiment is 25μm, the surface hardness of the TiAl alloy with the high-temperature antioxidant and wear-resistant coating on the surface is 1400HV, the wear resistance is improved by more than 1 times, and after high-temperature oxidation at above 1000°C for 100h, there is no slight discoloration on the surface, and the coating does not peel off.
[0046] like Figure 1 As shown, the high temperature oxidation resistant and wear resistant coating on the surface of the TiAl alloy substrate in this embodiment includes a diffusion layer and a diffusion layer deposited on the surface of the TiAl alloy substrate, and the high temperature oxidation resistant and wear resistant coating is connected to the substrate through a transition layer, and there is an interface between the transition layer and the diffusion layer; further detection shows that the diffusion layer and the diffusion layer are formed by alloy elements sputtered by bombardment of the Zr-Cr-Y alloy target and deposited and diffused onto the surface of the TiAl substrate, the main components of the diffusion layer are Cr, Zr, Ti, and Y, the main components of the diffusion layer are Ti, Cr, Zr, and Y, the main components of the interface are Ti, Al, Zr, Cr, and Y, and the Cr element content is reduced, and the remaining components are similar to the diffusion layer, and the composition of the transition layer is mainly composed of matrix elements Ti and Al, and contains a small amount of target elements Cr, Zr, and Y, and there is a small amount of Cr element segregation. During the oxidation process of the coating, as the oxidation time increases, O gradually diffuses from the diffusion layer to the inside, and Cr and Zr in the diffusion layer, diffusion layer and interface form an oxide film of Cr2O3 and ZrO2. The dense oxide film effectively prevents oxygen from diffusing inward, thereby improving the high-temperature oxidation resistance of the TiAl alloy substrate.
[0047] Example 4
[0048] This embodiment includes the following steps:
[0049] Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy using a surface grinder to remove the surface oxide layer, then place it in an ultrasonic cleaning machine filled with anhydrous ethanol for ultrasonic cleaning for 20 minutes to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used;
[0050] Step 2: ultrasonic impact strengthening is performed on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer; the step length of the ultrasonic impact strengthening is 0.06 mm, the pressure is 0.4 MPa, the number of impacts is 30 times, the frequency is 30 kHz, and the amplitude is 10 μm;
[0051] Step 3: polish the TiAl alloy with the modified layer in step 2 with 400#, 800# and 1000# sandpapers in turn, then ultrasonically clean it with deionized water for 5 minutes, then ultrasonically clean it with ethanol solution for 5 minutes, and blow dry it with cold air for later use;
[0052] Clean the double glow plasma metallurgical equipment and tooling, then place the spare TiAl alloy with the modified layer as a substrate on the workbench of the double glow plasma metallurgical equipment, use the Zr-Cr-Y alloy as the target, and adopt the double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metallized coating. The specific process is: open the argon valve to introduce argon, turn on the power at the same time, adjust the gas pressure to 70Pa, the cathode voltage to 700V, the source voltage to 1000V, the insulation temperature to 950℃, the insulation time to 4h, close the argon valve after the insulation is completed, cool it to below 150℃ with the furnace and take it out to obtain a TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface; the Zr-Cr-Y alloy is composed of the following components in percentage by mass: Zr 40%, Cr 57%, and Y3%.
[0053] After testing, the thickness of the high-temperature antioxidant and wear-resistant coating on the surface of the TiAl alloy in this embodiment is 30μm, the surface hardness of the TiAl alloy with the high-temperature antioxidant and wear-resistant coating on the surface is 1200HV, the wear resistance is improved by more than 1 times, and after high-temperature oxidation at above 1000°C for 100h, there is no slight discoloration on the surface, and the coating does not peel off.
[0054] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface, characterized in that: The method comprises the following steps: Step 1, pretreatment: polish the surface to be impacted of the TiAl alloy to remove the surface oxide layer, then perform ultrasonic cleaning to remove the residue and oil stains on the polished surface, dry it, wrap it with absorbent cotton, seal it in a sealed bag, and place it in a drying dish to prevent it from contacting the air and oxidizing again, so as to obtain the TiAl alloy to be used; Step 2: performing ultrasonic impact strengthening on the impact surface of the TiAl alloy to be used in step 1 to obtain a TiAl alloy with a modified layer; Step 3: Grind, clean and dry the TiAl alloy with the modified layer in step 2, and then place it as a substrate on the workbench of the double glow plasma metallurgical equipment. Use Zr-Cr-Y alloy as the target and adopt double glow plasma metallization process to perform surface metallization treatment on the substrate to form a metal-infiltrated coating. After cooling, take it out to obtain a TiAl alloy with a high-temperature antioxidant and wear-resistant coating on the surface.
2. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The polishing treatment in step 1 is performed using a surface grinder, and the ultrasonic cleaning is performed using an ultrasonic cleaning machine filled with anhydrous ethanol, and the ultrasonic cleaning time is 20 minutes.
3. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The ultrasonic impact strengthening in step 2 has a step size of 0.06 mm, a pressure of 0.4 MPa, an impact number of 1 to 30 times, a frequency of 20 kHz to 30 kHz, and an amplitude of 5 μm to 10 μm.
4. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: In step 3, the TiAl alloy with the modified layer is polished with 400#, 800#, and 1000# sandpapers in sequence, and then ultrasonically cleaned with deionized water for 5 minutes, and then ultrasonically cleaned with an ethanol solution for 5 minutes, and dried with cold air for later use.
5. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The Zr-Cr-Y alloy in step 3 is composed of the following components in percentage by mass: Zr 30% to 50%, Cr 45% to 75%, and Y 0.5% to 5%.
6. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The process of surface metallization treatment described in step three is: open the argon valve to introduce argon, turn on the power at the same time, adjust the gas pressure to 30Pa~70Pa, the cathode voltage to 500V~700V, the source voltage to 800V~1000V, the insulation temperature to 800℃~950℃, and the insulation time to 3h~6h; the cooling is furnace cooling to below 150℃.
7. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The thickness of the high temperature oxidation resistant and wear resistant coating in step three is 20 μm to 30 μm.
8. The method for preparing a high temperature oxidation resistant and wear resistant coating on a TiAl alloy surface according to claim 1, characterized in that: The surface hardness of the TiAl alloy with the high-temperature oxidation-resistant and wear-resistant coating on the surface described in step 3 is 1500HV to 1800HV, and the coating does not peel off after high-temperature oxidation above 1000°C for 100h.
Citation Information
Cited By
Raw material of ion plating target material and preparation method thereof
CN120210597A
